Understanding Why Women Knit: Finding Creativity and "Flow". (2nd January 2018) - Lampitt Adey, Kate
Abstract: Knitters can be spotted in cafés, on trains, and browsing boutique yarn stores. There is some consensus that people find knitting a relaxing and fulfilling hobby, but there is limited empirical evidence as to exactly why this is the case. This article will argue that Csikszentmihalyi's ([1992] 2002 ) theory of creative "flow" offers us a sound explanation for why and how knitting is beneficial. Csikszentmihalyi argues that "flow" experiences involve devoting full attention to the activity, a balance between challenge and accessibility and a sense of control. These key elements make creativity activities engaging and satisfying. This article draws on a qualitative research project investigating why women knit. This used a staged design influenced by grounded theory. The final stage of this research involved in-depth interviews with 30 women knitters living in Edinburgh. Interviews were recorded and transcribed, and thematically analyzed with support from QSR*NVivo. Data analysis suggested that women identified benefits from knitting related to both the knitting process and knitted product, and described positive experiences very closely related to those conceptualized by Csikszentmihalyi as "flow." These included a distraction from worries, engagement in a problem-solving process, and a sense of autonomy. Understanding the benefits associated with "flow" experiences may also be key to making sense of the investment some women make in knitting.